2017
DOI: 10.15252/embj.201797155
|View full text |Cite
|
Sign up to set email alerts
|

Guanylyl cyclase‐G is an alarm pheromone receptor in mice

Abstract: Many animals respond to threats by releasing alarm pheromones (APs) that warn conspecifics. In mice, detection of the AP 2-sec-butyl-4,5-dihydrothiazole (SBT) is mediated by chemosensory neurons residing in the Grueneberg ganglion (GG) of the anterior nasal region. Although the molecular mechanisms underlying activation of GG neurons by SBT and other substances are still unclear, recent studies have reported an involvement of the transmembrane guanylyl cyclase (GC) subtype GC-G in chemosensory signaling in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Our understanding of the interplay between the pathways processing GG-induced fear-like responses and those encoding food-odorant information remains to be completed. GG neurons use multi-signaling pathways, principally linked to bitter taste signaling 28 and GCG cascades 18 to detect a large repertoire of chemical danger cues 28,29 . Interestingly, in GC-D neurons, a similar encoding strategy occurs 14 making it also sensitive to fatty acids, steroid hormones as well as to some GG-related cues such as pyrazines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of the interplay between the pathways processing GG-induced fear-like responses and those encoding food-odorant information remains to be completed. GG neurons use multi-signaling pathways, principally linked to bitter taste signaling 28 and GCG cascades 18 to detect a large repertoire of chemical danger cues 28,29 . Interestingly, in GC-D neurons, a similar encoding strategy occurs 14 making it also sensitive to fatty acids, steroid hormones as well as to some GG-related cues such as pyrazines.…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that these danger and warning cues are detected in a specialized olfactory subsystem, the Grueneberg ganglion 9 , 15 (GG). They generate, in the recipient mouse, stereotypical fear-related behaviors, such as freezing and risk assessment as well as stress-related systemic responses 15 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Ace2 is strongly expressed in a specific area of the main olfactory epithelium (MOE), the dorsal part (MOED) which is directly exposed to the environment and specialized in sensing volatile chemical cues 14,15 . Moreover, we observed a previously unreported expression of Ace2, in the most rostral sensory subsystem, the Grueneberg ganglion (GG), mostly implicated in volatile danger cues detection [34][35][36] and in the circumvallate taste papilla (CV) involved in water-soluble tastant perception 29 . Interestingly, this specific pattern of Ace2 expression seems to be correlated with the mode of viral dissemination (volatile suspensions of viral droplets 25 ), as only a limited expression of Ace2 is found in the vomeronasal organ (VNO) and in the septal organ of Masera (SO), considered to be implicated in pheromonal and retronasal communications via indirect and only limited access to the environment 30 .…”
Section: Sars-mentioning
confidence: 94%
“…In a follow‐up study, Brechbuhl and colleagues identified 2‐sec‐butyl‐4,5‐dihydrothiazole (SBT) as the alarm pheromone that activated GG cells, elicited avoidance, and raised blood pressure. The last two effects required transmembrane guanylyl cyclase G . The components of predator odors, TMT from fox feces, and 2‐PT from the stoat anal gland, act similarly with the APs by activating GG .…”
Section: Neuronal Pathways For Fear Buffering and Facilitationmentioning
confidence: 99%